THE INFLUENCE OF SOCIO-ECONOMIC CONDITIONS ON CUSTOMERS' DECISIONS TO USE SUBSIDIZED KPR AT THE BTN SYARIAH KCP BUKITTINGGI BANK - Mysarah Mysarah; Romi Iskandar; Sri Ramadhani (Jurnal Scientia, 2023)
The cost factor can cause the choice of home financing by customers, because costs are required to realize financing at the bank. Customers consider costs a necessity, so each bank has different fee offers. Subsidized mortgages are in good development, but with their development not being too much of a concern to the public for the subsidized mortgages themselves, the City of Bukittinggi also has a Muslim majority so the researchers decided to research in the City of Bukittinggi to provide more information to the public about Islamic banking in the City of Bukittinggi. The research aims to determine the influence of socio-economic conditions on customers' decisions to use subsidized mortgages at the BTN Syariah KCP Bukittinggi bank. In this study, researchers used the Partial Least Square (PLS) approach to analyze data. PLS is a component- or variant-based Structural Equation Modeling (SEM) model. This study used a sample of 100 respondents or subsidized mortgage customers at the BTN Syariah KCP Bukittinggi bank. The results of this study stated that the socio-economic condition variable had a p-value of 0.003 and a statistical T value of 4.336. So it can be concluded that socio-economic conditions have a positive influence with a path coefficient value of 0.426 and are significant on the decisions of BTN Syariah KCP Bukittinggi customers. So it can be concluded that socio-economic conditions influence the customer's decision to use subsidized mortgages at the BTN Syariah KCP Bukittinggi bank.